The Influence of Instagram Social Media and Product Quality on Purchase Decisions on CV Shanjaya Group Webbing Tangerang - Retnaningrum Sri Puji Wahyuningsih; Elizabeth Tika Kristina Hartuti (Bhinneka Multidisiplin Journal, 2026)
The purpose of this study is to determine the influence of Instagram social media and product quality on purchase decisions on CV Shanjaya Group Webbing Tangerang. The method used is quantitative. The sampling technique used the slovin formula and a sample of 93 respondents was obtained. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The population in this study is consumers of CV Shanjaya Group Webbing Tangerang and the number of saturated samples amounted to 93 respondents. The method of data collection is through questionnaires with a likert scale, observation, and literature study. The results of this study are that Instagram social media has a significant effect on purchasing decisions with a determinationcoefficient of 28.1% and a hypothesis test obtained by tcal > ttable or (8.026 > 1.98667). Product quality had a significant effect on the purchase decision with a determination coefficient of 21.4% and the hypothesis test was obtained > ttable or (7.663 > 1.98667). Instagram social media and product quality simultaneously had a significant effect on purchase decisions by obtaining the regression equation Y = 17.104 + 0.394X1 + 0.271X2, nilai coefficient of determination of 54.2% while the remaining 45.8% was influenced by other factors. The hypothesis test obtained the value of Fcal > Ftabel or (53.262 > 3.10).